Pemberdayaan Aparat Desa Dalam Optimalisasi Program Kerja Pada RKP dan RPJM Desa Sebagai Upaya Percepatan Pencapaian SDGs Untuk Mendukung Program Desa Membangun - Ahmad, Jusna; Febriyanti, Febriyanti (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
Lobuto Village, Biluhu District, Gorontalo Regency has a lot of potential that needs to be developed and preserved. In order to accelerate the development of Lobuto Village in accordance with Law No. 25 of 2004 concerning the national, regional and village development planning system, strategic steps are needed as an effort for the sustainable development of Lobuto village, namely through the village development program in achieving the SDGs.Therefore, through the Community Service Program the Thematic Village Community Service Program, it is hoped that it can help analyze work programs that are right on target and really needed by the Lobuto Village community to be implemented with the development of the latest innovations and technology so that they can be used directly for the community to improve the economy , community welfare, socio-cultural improvement and health to support the Village Build program in achieving the SDGs. Based on the results of the analysis and assessment in the field, a program of activities that are very urgent and considered appropriate to the needs of the Lobuto Village community are formulated, namely: (1). Coastal tourism development, (2). Management and marketing of fishery products, (3). Planning for making village libraries, (4). Construction of a Waste Bank and supported by several other additional programs such as (1). Tumbilotohe implementation and (2). Entertainment activities for the community. The program of activities will be included in the development work plan (RKP) of Lobuto Village, Biluhu District, Gorontalo Regency.